2021
DOI: 10.1093/iob/obab003
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Morphology, Functional Trade-offs, and Evolutionary Dynamics in a Clade of Open-Ocean Fishes (Perciformes: Bramidae)

Abstract: When novel or extreme morphologies arise, they are oft met with the burden of functional trade-offs in other aspects of anatomy, which may limit phenotypic diversification and make particular adaptive peaks inaccessible. Bramids (Perciformes: Bramidae) comprise a small family of 20 extant species of fishes, which are distributed throughout pelagic waters worldwide. Within the Bramidae, the fanfishes (Pteraclis and Pterycombus) differ morphologically from the generally stout, laterally compressed species that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 99 publications
0
22
0
Order By: Relevance
“…Adaptive trade‐offs impose fundamental constraints on phenotypic evolution and shape biodiversity patterns by allowing the coexistence of taxa along environmental gradients (Careau et al, 2010 ; Finstad et al, 2011 ). Although morphological and behavioral trade‐offs have received considerable attention (e.g., cranial versus fin morphology: Gilbert et al, 2021 ; shy versus bold behaviors: Stamps, 2007 ), physiological trade‐offs, and their impacts on fitness correlates (e.g., growth and survival: Monaghan et al, 2009 ) may also drive considerable phenotypic and ecological differentiation (Braendle et al, 2011 ; Careau & Garland, 2012 ). Cryptic trade‐offs among competing physiological processes, however, are less well studied, despite the potential to generate significant biological diversity in nature (Agrawal et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive trade‐offs impose fundamental constraints on phenotypic evolution and shape biodiversity patterns by allowing the coexistence of taxa along environmental gradients (Careau et al, 2010 ; Finstad et al, 2011 ). Although morphological and behavioral trade‐offs have received considerable attention (e.g., cranial versus fin morphology: Gilbert et al, 2021 ; shy versus bold behaviors: Stamps, 2007 ), physiological trade‐offs, and their impacts on fitness correlates (e.g., growth and survival: Monaghan et al, 2009 ) may also drive considerable phenotypic and ecological differentiation (Braendle et al, 2011 ; Careau & Garland, 2012 ). Cryptic trade‐offs among competing physiological processes, however, are less well studied, despite the potential to generate significant biological diversity in nature (Agrawal et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, others have found that quantifying evolutionary rates by using the initial principal component axes can bias the results to mirror an EB evolutionary model (Uyeda et al, 2015). We, therefore, urge caution in these interpretations and refer to our previous paper (Gilbert et al, 2021) for other results supporting an EB model.…”
Section: Patterns Of Morphological Variation Are Similar Between Juve...mentioning
confidence: 79%
“…Methods for acquiring both geometric morphometric data and linear measures are described in detail in Gilbert et al (2021). In short, the left lateral surfaces of specimens were imaged and then digitized using STEREOMORPH (Olsen & Westneat, 2015) in R (R Core Team, 2018).…”
Section: Morphometric Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout an organism's lifetime, most structures will serve more than one function. This multifunctionality is often framed as a core constraint of phenotypic evolution: the more functions a structure directly serves, the more the evolution of that structure is constrained by the increasingly narrow range of phenotypes that will sufficiently serve all of those functions (Corn et al, 2021;Gilbert et al, 2021). Most of the functions an animal must perform -feeding, respiration, locomotion, and reproduction -do not change, even if their particular mode (e.g.…”
Section: Introductionmentioning
confidence: 99%